New typifications and synonyms in Senecio ser. Culcitium and related taxa (Asteraceae, Senecioneae) - Salomón, Luciana; Freire, Susana Edith (Phytotaxa, 2014)
Seven lectotypes and three neotypes are designated for ten names applicable to species of Senecio sect. Senecio ser. Culcitium. Our results show that Senecio culcitenellus and S. vaginifolius are conspecific with S. magellanicus, while S. roripifolius is considered a synonym of S. aspleniifolius.